THE FORMATION OF POLITICAL AND ECONOMIC RELATIONS BETWEEN THE BUKHARA KHANATE AND THE TSARDOM OF RUSSIA (LATE 16th – FIRST HALF OF THE 17th CENTURY) - Normuratov O‘. J. (TARIXIY TADQIQOTLAR, 2026)
This article analyzes the dynamics of the formation of diplomatic relations, the characteristics of embassy protocol, and the stages of development of bilateral trade ties between the Bukhara Khanate and the Tsardom of Russia in the last quarter of the 16th and the first half of the 17th centuries. The study elucidates changes in regional geopolitics during the crisis of the Sheybanids and the rise to power of the Ashtarkhanid dynasty, the foreign policy strategy of the Romanov dynasty, as well as protocol conflicts that arose during the exchange of envoys. In particular, a scientific assessment is provided regarding the missions of diplomatic representatives such as Ivan Khokhlov, Muhammad Ali, and Anisim Gribanov, along with their political and economic outcomes.